A Dual Perspective of the Action of Lysine on Soybean Oil Oxidation Process Obtained by Combining 1H NMR and LC-MS: Antioxidant Effect and Generation of Lysine-Aldehyde Adducts - Ana S. Martin-Rubio; Patricia Sopelana; Fumie Nakashima; Takahiro Shibata; Koji Uchida; María D. Guillén (MDPI AG, 2019)
Little is still known about both the effect of amino acids on the oxidation course of edible oils and the modifications that the former may undergo during this process. Bearing this in mind, the objective of this work was to study the evolution of a system consisting of soybean oil with 2% of l-lysine under heating at 70 °C and stirring conditions, analyzing how the co-oxidation of the oil and of the amino acid affects their respective evolutions, and trying to obtain information about the action mechanism of lysine on soybean oil oxidation. The study of the oil progress by 1H Nuclear Magnetic Resonance (1H NMR) showed that the presence of lysine noticeably delays oil degradation and oxidation products generation in comparison with a reference oil without lysine. Regarding lysine evolution, the analysis by 1H NMR and Liquid Chromatography-Mass Spectrometry of a series of aqueous extracts obtained from the oil containing lysine over time revealed the formation of lysine adducts, most of them at the position, with n-alkanals, malondialdehyde, (E)-2-alkenals, and toxic oxygenated α β-unsaturated aldehydes. However, this latter finding does not seem enough to explain the antioxidant action of lysine.